2005
DOI: 10.1093/ps/84.9.1477
|View full text |Cite
|
Sign up to set email alerts
|

Culture of chicken embryos in surrogate eggshells

Abstract: The chick embryo is a classical model to study embryonic development. However, most researchers have not studied the effect of embryonic manipulation on chick hatchability. The objective of this study was to determine the effect of egg orientation and type of sealing film on the hatchability of cultured embryos. Windows were made in the small end of recipient surrogate chicken eggshells, and donor embryos were placed into the recipient eggshell for the first 3 d of incubation. Survival over the first 3 d was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 20 publications
2
57
1
Order By: Relevance
“…The preincubation period until the transfer of embryos to the culture vessel influenced the viability on culture day 8 as well as the successful embryo transfer to the culture vessel. The transfer of embryos to the culture vessel was considered to be optimal on day 3 (Rowlett and Simkiss, 1987;Borwornpinyo et al, 2005). In the present study, different egg preincubation periods between 48 h and 56 h exhibited variable effects on viability.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The preincubation period until the transfer of embryos to the culture vessel influenced the viability on culture day 8 as well as the successful embryo transfer to the culture vessel. The transfer of embryos to the culture vessel was considered to be optimal on day 3 (Rowlett and Simkiss, 1987;Borwornpinyo et al, 2005). In the present study, different egg preincubation periods between 48 h and 56 h exhibited variable effects on viability.…”
Section: Discussionmentioning
confidence: 72%
“…The hatchability of embryos cultured under these conditions was 57.1% (8 out of 14) when taking the number of surviving embryos at day 17 as 100%. Borwornpinyo et al (2005) reported that chicken embryo culture method using turkey eggshells and Handi-Wrap as culture vessels before transitioning to Perry's System III exhibited 81.1% hatchability when the number of surviving embryos at day 3 was taken as 100%. Although our culture method does not use surrogate eggshells, a high hatchability of more than 50% was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chick embryo can be visualized in ovo 16 but with poor accessibility for experimental manipulations and limited visibility for transmission light microscopy imaging. Therefore, several techniques have been proposed to culture chick embryos ex ovo, either in whole yolk culture systems 13,[17][18][19] or as explant cultures 1,[20][21][22][23] . In whole yolk culture systems, the embryo remains on top of the intact yolk, and the whole content of the egg is transferred to another container for incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent transgenic reptiles can be useful when an experimental repellant is sprayed directly onto the reptile, and the behavior of a fluorescent reptile can be more easily monitored than a wild-type snake. Lastly, the gecko embryo is amiable to manipulation in much the same way that the chick embryo is amiable for manipulation (Borwornpinyo et al, 2005) making it possible to inject cells from the transgenic geckos into wild-type geckos to analyze cell fate and plasticity in the embryonic environment.…”
Section: Introductionmentioning
confidence: 99%